2020
DOI: 10.1007/s40843-020-1269-9
|View full text |Cite
|
Sign up to set email alerts
|

15.3% efficiency all-small-molecule organic solar cells enabled by symmetric phenyl substitution

Abstract: Synergistic optimization of donor-acceptor blend morphologyis a hurdle in the path of realizing efficient non-fullerene small-molecule organic solar cells (NFSM-OSCs) due to the anisotropic conjugated backbones of both donor and acceptor. Therefore, developing a facile molecular design strategy to effectively regulate the crystalline properties of photoactive materials, and thus, enable the optimization of blend morphology is of vital importance. In this study, a new donor molecule B1, comprising phenyl-substi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
157
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 163 publications
(163 citation statements)
references
References 50 publications
6
157
0
Order By: Relevance
“…Hou and coworkers studied the effect of SVA on all small molecule OSCs (B1:BO‐4Cl and benzodithiophene terthiophene rhodanine (BTR):BO‐4Cl). [ 76 ] Solvent‐annealed B1:BO‐4Cl blend film showed an improved donor and acceptor crystallinity, as well as a dominant face‐on orientation. The face‐on ratio was 94% in the blend film, whereas it was only 2% in the pristine B1 film.…”
Section: Probing the Active Layer Morphology With Gisaxs And Giwaxsmentioning
confidence: 99%
“…Hou and coworkers studied the effect of SVA on all small molecule OSCs (B1:BO‐4Cl and benzodithiophene terthiophene rhodanine (BTR):BO‐4Cl). [ 76 ] Solvent‐annealed B1:BO‐4Cl blend film showed an improved donor and acceptor crystallinity, as well as a dominant face‐on orientation. The face‐on ratio was 94% in the blend film, whereas it was only 2% in the pristine B1 film.…”
Section: Probing the Active Layer Morphology With Gisaxs And Giwaxsmentioning
confidence: 99%
“…Gaining from cooperation of the novel donor: acceptor (D:A) material synthesis and device fabrication, tremendous strides have been achieved on the power conversion efficiencies (PCEs) of organic solar cells (OSCs). [ 1–9 ] In non‐fullerene systems, significant PCEs were usually obtained based on polymer donors due to the polymers have a stronger ability to form an interpenetrating networks in bulk‐heterojunctions (BHJ) for charge carrier transport in comparison with small molecular donors. [ 10–15 ] Compared with polymers, small molecular donors have advantages of high purity and definite molecular structures.…”
Section: Introductionmentioning
confidence: 99%
“…[ 25–27 ] Therefore, tuning the morphology of the active layer is one of the most critical factors which need to be considered for the performance improvement for ASM‐OSCs. [ 7,22,28–30 ] For matching with the small molecular acceptors such as Y6, we reported a small molecular donor ZR1 based on dithieno[2,3‐d:2ʹ,3ʹ‐dʹ]benzo[1,2‐b:4,5‐bʹ]dithiophene (DTBDT) unit. Binary all‐small‐molecule OSC based on ZR1:Y6 blend achieved the highest efficiency of 14.34% by optimizing their hierarchical morphologies, in which the donor or acceptor rich domains with size up to ca.…”
Section: Introductionmentioning
confidence: 99%
“…8,23,24 However, SM donors sporadically succeeded with several advantages such as high crystallinity, rapid aggregation pathways, controllable energy levels, etc., and as a result, assisting the significant enhancement of PCEs in recent years. [25][26][27][28][29][30][31][32][33][34][35][36][37][38] However, the combination of a SM donor and a SM acceptor has been a bottleneck hindering the performance so far due to their high crystallinity and unfavourable phase separation and morphologies. 25,39 Recently, Wei et al reported an A-p-D-p-A structural narrow bandgap SM donor based on a larger coplanar core DTBDT and achieved the highest PCE of 14.34% at that time for binary all SM OSCs by optimizing their hierarchical morphologies.…”
Section: Introductionmentioning
confidence: 99%